Child Maltreatment: Optimizing Recognition and Reporting by School Nurses. (May 2017) - Jordan, Kathleen S.; MacKay, Peggy; Woods, Stephanie J.
School nurses perform a crucial role in the prevention, identification, intervention, and reporting of child maltreatment. The purpose of this article is to share the highlights of a research project conducted to (a) examine the effectiveness of an educational intervention program in increasing the knowledge, confidence, and self-efficacy in school nurses regarding children at risk of maltreatment; and (b) discover issues surrounding the comfort level engaging with children, communicating with teachers and other personnel, and ethical issues. The study consisted of two phases. Phase 1 was a face-to-face evidenced-based educational intervention. Focus groups implemented in Phase 2 discovered specific concerns of school nurses. Results indicate a significant increase in school nurse knowledge, confidence, and self-efficacy related to children at risk. Five themes were identified from the focus groups: the importance of interprofessional collaboration, identifiers of children at risk of maltreatment, the role of the school nurse as a mentor and leader, the importance of advancing one's knowledge and skill set, and constraints faced by school nurses.